2018
DOI: 10.1108/heed-01-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation at home for tourism training programmes: case studies from Vietnam

Abstract: Purpose Tourism is one of the most notable features of the contemporary globalised world. The tourism industry is becoming increasingly vital to the economy of many developing and developed countries around the globe. The demand of the tourism industry has posed a challenge for tourism training providers to move towards a more responsive and internationalised curriculum to enhance work readiness for tourism graduates who are expected to work with an increased number of international tourists. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The focus is on isolated experiences and activities, which are largely disconnected from the program of study, rather than on the systematic development of the whole program. In conclusion, the findings are in accordance with the results of Khuong and Tran (2018) who concluded that IoC in higher tourism education is still fragmented and based on ad hoc practices.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The focus is on isolated experiences and activities, which are largely disconnected from the program of study, rather than on the systematic development of the whole program. In conclusion, the findings are in accordance with the results of Khuong and Tran (2018) who concluded that IoC in higher tourism education is still fragmented and based on ad hoc practices.…”
Section: Discussionsupporting
confidence: 90%
“…Leung, Wen, and Jiang (2018) compared the differences in curriculum development of undergraduate hospitality programs in the U.S., the UK and Australia with suggestions of creating international hospitality program standards to make hospitality programs comparable across countries. Khuong and Tran (2018) analyzed how internationalization has been implemented in the tourism training programs in Vietnam mainly focusing on IaH.…”
Section: Internationalization Of the Curriculum In The Tourism Contextmentioning
confidence: 99%